Updated descriptions of the nematocysts of the scyphozoan jellyfish Cyanea nozakii Kishinouye, 1891 (Cnidaria, Scyphozoa). (November 2020) - Yue, Yang; Xue, Wei; Yu, Huahua; Li, Rongfeng; Li, Pengcheng
Abstract: Nematocysts are typical cnidarian organelles that can discharge and release venom under physicochemical stimuli for predation and defense. Cyanea nozakii Kishinouye, 1891, a dominant jellyfish-blooming species in Chinese coastal waters, possesses numerous stinging nematocysts on its tentacles, and causes many envenomations every year. However, detailed taxonomic information of nematocysts in C. nozakii is elusive. In the present study, the morphological characteristics of nematocysts from C. nozakii were examined by combined light and scanning-electron microscopy. Five nematocyst types were revealed in the cnidome of C . nozakii, including common nematocyst types identified in Scyphozoa: atrichous isorhizas (a-atrich/O-atrich), microbasic euryteles, and microbasic birhopaloids type II. Importantly, two seldom reported types, microbasic b-mastigophores and microbasic birhopaloids type I, were also found, for the first time, in the cnidome of C. nozakii . This study contributes to understanding of the cnidome of C. nozakii, and the present study strongly suggests that the nematocysts of Scyphozoa are more diverse and complex than previously reported, which sheds new light on the nematocyst types in Scyphozoa species. Highlights: The nematocysts of jellyfish Cyanea nozakii were identified using combined light and scanning-electron microscopy. The updated cnidome of C. nozakii included atrichous isorhizas, euryteles, birhopaloids and microbasic b-mastigophores. Microbasic b-mastigophores and microbasic birhopaloids type I were identified, for the first time, in C. nozakii. This study strongly suggests that the nematocysts of Scyphozoa are more diverse and complex than previously reported.